Impact of Covid-19 Pandemic on Ministry of Religious Affairs Policy in Entrepreneurial Development of Pondok Pesantren - Fatmawati, Fatmawati; Mulazid, Ade Sofyan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2021)
This study aims to analyze the impact of the Covid-19 pandemic on the Ministry of Religious Affairs policies in the development of entrepreneurial pondok pesantren (Islamic boarding schools). This research method, using a qualitative descriptive approach. The primary data source comes from interviews and activity reports obtained directly from the office of the Directorate of Diniyah Education and Pondok Pesantren of the Ministry of Religious Affairs and other relevant documentation. Data analysis techniques using descriptive qualitative analysis, intended to find out the social reality of the Ministry of Religious Affairs as policymakers of entrepreneurial pondok pesantren assistance programs affected by the Covid-19 pandemic that was constructed by the mass media through advertising creators and newsmakers. The results showed that the Covid-19 pandemic also affected the economic life of pesantren huts, so policies and strategic measures were needed in developing vocational life skill education programs designed to support the sustainable progress of pesantren business units. The entrepreneurial and vocational lifeskill pondok pesantren movement initiated by the Ministry of Religious Affairs in collaboration with Bank Indonesia has broader implications on aspects of the reach of ummah economic empowerment and pesantren economic independence improving the welfare of the surrounding community. Penelitian ini bertujuan untuk menganalisis dampak pandemi Covid-19 terhadap kebijakan Kementerian Agama dalam pengembangan entrepreneurial pondok pesantren. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif. Sumber data primer berasal dari wawancara dan laporan kegiatan yang diperoleh langsung dari kantor Direktorat Pendidikan Diniyah dan Pondok Pesantren Kementerian Agama, serta dokumentasi lainnya yang relevan. Tehnik analisis data menggunakan analisis kualitatif deskriptif, dimaksudkan untuk mengetahui realitas sosial Kementerian Agama sebagai pengambil kebijakan program bantuan entrepreneurial pondok pesantren terdampak akibat pandemi Covid-19 yang dikonstruk media massa melalui pencipta iklan dan pembuat berita. Hasil penelitian menunjukan bahwa pandemi Covid-19 ikut berpengaruh pada kehidupan ekonomi pondok pesantren, sehingga diperlukan kebijakan dan langkah-langkah strategis dalam megembangkan program pendidikan lifeskill vokasional pondok pesantren yang dirancang untuk mendukung kemajuan unit bisnis pesantren secara berkelanjutan. Gerakan entrepreneurial dan pendidikan lifeskill vokasional pondok pesantren yang digagas Kementerian Agama bekerjasama dengan Bank Indonesia ini, memiliki implikasi yang lebih luas pada aspek jangkauan pemberdayaan ekonomi umat dan kemandirian ekonomi pesantren, serta peningkatan kesejahteraan masyarakat sekitar.